Touch gloss oil and application thereof

By combining transparent polyether polyurethane and epoxy-modified acrylic resin, the adhesion and abrasion resistance issues of tactile oil on BOPP film were solved, forming a coating with excellent performance and enhancing the decorative effect of packaging materials.

CN120842903APending Publication Date: 2025-10-28RR DONNELLEY (GUANGDONG) PRINTING SOLUTIONS LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510961392.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-11
Publication Date
2025-10-28

AI Technical Summary

Technical Problem

Existing UV-sensitive oils have poor tactile effects on BOPP films and are prone to color cracking. Water-based tactile oils have insufficient adhesion to BOPP films and cannot pass abrasion resistance and anti-staining tests.

Method used

A coating is formed by combining transparent polyether polyurethane, epoxy-modified acrylic resin, ethanol, dimethylsiloxane, polyethylene wax emulsion, silicone defoamer, silicone hand feel agent and polyethylene oxide. Through the interaction of different components, a coating is formed, which improves adhesion and wear resistance.

Benefits of technology

It achieves excellent water resistance, hot water resistance, anti-adhesion, toughness, strong touch, and good wear resistance on BOPP film, and is also environmentally friendly, low in volatility, and energy-saving, enhancing the decorative effect of packaging materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120842903A_ABST
    Figure CN120842903A_ABST
Patent Text Reader

Abstract

The invention provides touch gloss oil and application thereof. The touch gloss oil is prepared from transparent polyether polyurethane, epoxy modified acrylic resin, ethanol, dimethyl siloxane, polyethylene wax emulsion, an organic silicon defoaming agent, an organic silicon feeling agent and polyoxyethylene. According to the touch gloss oil, the transparent polyether polyurethane is combined with the epoxy modified acrylic resin, and through mutual influence of different component formulas, the problems that the touch gloss oil applied to the BOPP film is poor in wear resistance and scratch resistance, explosive in color at folding positions and insufficient in adhesive force are effectively solved, and meanwhile the touch gloss oil has the advantages of being environmentally friendly in production and preparation process, safe, low in volatilization and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of tactile varnish technology, and more particularly to a tactile varnish and its application in packaging materials, including paper or paperboard with a coating formed by the tactile varnish. Background Technology

[0002] Tactile varnishes are gaining popularity in the packaging and printing industry, especially in gift packaging. Existing tactile varnishes include UV tactile varnishes and water-based tactile varnishes. UV tactile varnishes offer poor tactile properties when applied to biaxially oriented polypropylene (BOPP) glossy film, and are prone to color cracking and splitting at fold lines. Water-based tactile varnishes exhibit poor adhesion to BOPP film and fail abrasion resistance and anti-scratch tests.

[0003] The content of the background section is merely the technology known to the inventor and does not necessarily represent the prior art in this field. Summary of the Invention

[0004] In view of at least one of the problems of the prior art, the first objective of this application is to provide a tactile varnish, characterized in that it comprises: transparent polyether polyurethane, epoxy-modified acrylic resin, ethanol, dimethylsiloxane, polyethylene wax emulsion, silicone defoamer, silicone hand feel agent and polyethylene oxide.

[0005] In some embodiments of this application, the tactile varnish comprises the following raw materials by weight percentage: 38-48 wt% transparent polyether polyurethane, 30-40 wt% epoxy modified acrylic resin, 3-9 wt% water, 3-8 wt% ethanol, 2-4.5 wt% dimethylsiloxane, 2-4.5 wt% polyethylene wax emulsion, 0.5-1.5 wt% silicone defoamer, 1.5-2.5 wt% silicone hand feel agent and 1-2 wt% polyethylene oxide.

[0006] In some embodiments of this application, the tactile varnish is made from the following raw materials by weight percentage: 42~46wt% transparent polyether polyurethane, 32~36wt% epoxy modified acrylic resin, 5~7wt% purified water, 4~6wt% ethanol, 3~4wt% dimethylsiloxane, 2.5~3.5wt% polyethylene wax emulsion, 1wt% silicone defoamer, 2wt% silicone hand feel agent and 1.5wt% polyethylene oxide.

[0007] In some embodiments of this application, the molecular weight of the transparent polyether polyurethane is 2500-2800.

[0008] In some embodiments of this application, the molecular weight of the epoxy-modified acrylic resin is 75,000 to 78,000.

[0009] In some embodiments of this application, the concentration of ethanol is greater than 90% wt.

[0010] In some embodiments of this application, the solid content of the polyethylene wax emulsion is 30-40 wt%.

[0011] A second objective of this application is to provide the application of any of the above-described tactile varnishes in packaging materials.

[0012] A third objective of this application is to provide a printed matter comprising a coating formed by any of the tactile varnishes described above.

[0013] This application uses transparent polyether polyurethane combined with epoxy-modified acrylic resin, and through the interaction of different component formulations, effectively solves the problems of poor abrasion and scratch resistance, easy color explosion at folds, and insufficient adhesion of tactile varnish applied to BOPP film. At the same time, its production process has the advantages of environmental protection, safety, and low volatility.

[0014] The tactile varnish provided in this application has a fast curing speed during application (printing process) and has excellent water resistance, hot water resistance, chemical resistance, anti-adhesion, toughness, strong tactile feel, good wear resistance, low volatility, energy saving and environmental protection, non-yellowing, low cost, and stable product quality, which is conducive to improving the decorative effect of packaging materials.

[0015] Additional aspects and advantages of the invention will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of the invention. Attached Figure Description

[0016] The accompanying drawings, which form part of this disclosure, are used to provide a further understanding of this disclosure. The illustrative embodiments of this disclosure and their descriptions are used to explain this disclosure and do not constitute an undue limitation of this disclosure. In the drawings: Figure 1 This is a schematic diagram of the process flow for preparing tactile varnish according to an embodiment of the present invention.

[0017] Figure 2 The diagram shows the abrasion resistance test results of a pair of printed materials prepared according to the present invention.

[0018] Figure 3 The diagram shows the anti-explosion color test results of a pair of printed materials prepared according to the present invention.

[0019] Figure 4 The figure shows the adhesion evaluation results of a pair of printed materials prepared according to the present invention. Detailed Implementation

[0020] In the following description, only certain exemplary embodiments are briefly described. As those skilled in the art will recognize, the described embodiments can be modified in various ways without departing from the spirit or scope of the invention. Therefore, the drawings and description are considered to be exemplary in nature and not restrictive.

[0021] The following disclosure provides many different embodiments or examples for implementing various structures of the invention. To simplify the disclosure, specific examples of components and arrangements are described below. These are merely examples and are not intended to limit the invention. Furthermore, reference numerals and / or letters may be repeated in different examples; such repetition is for simplification and clarity and does not in itself indicate a relationship between the various embodiments and / or arrangements discussed. In addition, examples of various specific processes and materials are provided in this invention, but those skilled in the art will recognize the application of other processes and / or the use of other materials.

[0022] Taking into account the measurements discussed and the errors associated with the measurement of a particular quantity (i.e., limitations of the measurement system), as used herein, “about” or “approximately” includes the stated value and means within an acceptable range of deviation from the particular value as determined by a person skilled in the art. For example, “about” may mean within one or more standard deviations, or within ±30%, ±20%, ±10%, or ±5% of the stated value.

[0023] The specific embodiments of the present invention will be described in more detail below with reference to the accompanying drawings and examples, so as to better understand the solution of the present invention and its advantages in various aspects. However, the specific embodiments and examples described below are for illustrative purposes only and are not intended to limit the present invention.

[0024] The tactile varnish provided in this application includes: transparent polyether polyurethane, epoxy-modified acrylic resin, ethanol, dimethylsiloxane, polyethylene wax emulsion, silicone defoamer, silicone hand feel agent, and polyethylene oxide.

[0025] Transparent polyether polyurethane is flexible and abrasion-resistant, and can be used as a coating and repair agent for BOPP films. Transparent polyether polyurethane has a soft and full feel; when blended with epoxy-modified acrylic resin, it increases flexibility, resulting in a more durable and shatter-resistant tactile varnish coating. The content of transparent polyether polyurethane used in this application can be 38-48 wt%. In some embodiments of this application, the content of transparent polyether polyurethane can be 38 wt%, 39 wt%, 40 wt%, 42 wt%, 43 wt%, 44 wt%, 45 wt%, 46 wt%, 47 wt%, or 48 wt%. A more preferred content is 42-46 wt%. Its molecular weight can be 2500-2800.

[0026] In this application, epoxy-modified acrylic resin is used to disperse transparent polyether polyurethane in water to form a uniform emulsion. The polar groups within the molecule generate cohesive and adhesive forces. Under suitable conditions, carboxyl and hydroxyl groups in the groups can participate in the reaction and crosslink with BOPP molecules, thereby increasing adhesion. The content of epoxy-modified acrylic resin used in this application can be 30-40 wt%. In some embodiments of this application, the content of epoxy-modified acrylic resin can be 30 wt%, 31 wt%, 32 wt%, 33 wt%, 34 wt%, 35 wt%, 36 wt%, 37 wt%, 38 wt%, 39 wt%, or 40 wt%. A more preferred content is 32-36 wt%. Its molecular weight can be 75,000-78,000.

[0027] The tactile varnish of this application also requires the use of some water, optionally purified water. Water molecules are polar, possessing strong cohesive forces and surface tension, and exhibiting significant capillary and adsorption phenomena, used to adjust the viscosity and leveling properties of the overall tactile varnish. The water content can be 3-9 wt%. In some embodiments of this application, the water content can be 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, or 9 wt%. Preferably, the water content is 5-7 wt%.

[0028] Ethanol is a volatile, colorless, and transparent liquid at room temperature and pressure. It is miscible with most organic solvents. The hydroxyl groups in its molecules can form hydrogen bonds, allowing it to quickly absorb moisture and increase the drying speed of the coating formed by the tactile varnish. In this application, the ethanol content can be 3-8 wt%. In some embodiments of this application, the ethanol content can be 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, or 8 wt%. Preferably, the content is 4-6 wt%. The concentration of ethanol used in this application can be greater than 90 wt%. Higher ethanol concentrations result in better performance.

[0029] Dimethylsiloxane possesses low surface tension, softness, and antistatic properties, enabling strong cross-linking of molecules. It also reduces viscosity and improves leveling, effectively mitigating intermolecular stress in resins. In this application, the content of dimethylsiloxane can be 2-4.5 wt%. In some embodiments of this application, the content of dimethylsiloxane can be 2 wt%, 2.5 wt%, 3 wt%, 3.5 wt%, 4 wt%, or 4.5 wt%. Preferably, the content is 3-4 wt%.

[0030] Polyethylene wax emulsions primarily function as fillers in coatings, improving coating feel, enhancing wear resistance, preventing sticking, and increasing gloss. They can form thin films that are microscopically very smooth and strongly reflect light, thus producing a glossy appearance. Polyethylene wax emulsions that produce a matte finish have larger particle sizes, forming a heterogeneous and microscopically uneven surface on the coating. In this application, the content of the polyethylene wax emulsion can be 2-4.5 wt%. In some embodiments of this application, the content of the polyethylene wax emulsion can be 2 wt%, 2.5 wt%, 3 wt%, 3.5 wt%, 4 wt%, or 4.5 wt%. Preferably, the solid content of the 2.5-3.5 wt% polyethylene wax emulsion can be 30-40 wt%. In some embodiments of this application, the solid content can be 32 wt%, 34 wt%, 36 wt%, 38 wt%, or 40 wt%. At these solid contents, the performance is superior.

[0031] Silicone defoamers can reduce bubbles in tactile varnishes during production and use. The surface tension of the silicone defoamer is much lower than that of the liquid film, allowing the silicone defoamer droplets to continuously spread and penetrate the liquid film surface. The localized liquid film continues to thin, eventually forming a bridge between the oil and water phases. Due to the significant difference in surface tension between the oil and water phases, the oil phase is stretched and thinned under the continuous pull of the surrounding water phase. Once the deformation exceeds a certain range, the liquid film is destroyed, leading to foam rupture. In this application, the content of the silicone defoamer can be 0.5~1.5 wt%. In some embodiments of this application, the content of the silicone defoamer can be 0.5 wt%, 1 wt%, or 1.5 wt%. Preferably, the content of the silicone defoamer is 1 wt%.

[0032] The silicone hand-feel agent prevents surface adhesion and is a nonionic, polyamino silicone-based microemulsion with good film-forming properties, enhancing hand-feel performance. In this application, the content of the silicone hand-feel agent can be 1.5~2.5 wt%. In some embodiments of this application, the content of the silicone hand-feel agent can be 1.5 wt%, 2 wt%, or 2.5 wt%. Preferably, the content of the silicone hand-feel agent is 2 wt%.

[0033] Polyethylene oxide (PEO) can increase wear and scratch resistance, and features high purity, good scratch resistance, narrow molecular weight distribution, and good dispersibility. It can improve the wear resistance, lubricity, and smoothness of printed surfaces. In this application, the PEO content can be 1-2 wt%. In some embodiments of this application, the PEO content can be 1 wt%, 1.5 wt%, or 2 wt%. Preferably, the PEO content is 1.5 wt%.

[0034] In some embodiments of this application, the tactile varnish comprises the following raw materials by weight percentage: 38-48 wt% transparent polyether polyurethane, 30-40 wt% epoxy modified acrylic resin, 3-9 wt% water, 3-8 wt% ethanol, 2-4.5 wt% dimethylsiloxane, 2-4.5 wt% polyethylene wax emulsion, 0.5-1.5 wt% silicone defoamer, 1.5-2.5 wt% silicone hand feel agent and 1-2 wt% polyethylene oxide.

[0035] In some embodiments of this application, the tactile varnish comprises the following raw materials by weight percentage: 42-46 wt% transparent polyether polyurethane, 32-36 wt% epoxy modified acrylic resin, 5-9 wt% water, 3-8 wt% ethanol, 2-4.5 wt% dimethylsiloxane, 2-4.5 wt% polyethylene wax emulsion, 0.5-1.5 wt% silicone defoamer, 1.5-2.5 wt% silicone hand feel agent and 1-2 wt% polyethylene oxide.

[0036] In some embodiments of this application, the tactile varnish comprises the following raw materials by weight percentage: 42~46wt% transparent polyether polyurethane, 32~36wt% epoxy modified acrylic resin, 5~7wt% purified water, 4~6wt% ethanol, 3~4wt% dimethylsiloxane, 2.5~3.5wt% polyethylene wax emulsion, 1wt% silicone defoamer, 2wt% silicone hand feel agent and 1.5wt% polyethylene oxide.

[0037] In some embodiments of this application, the tactile varnish is made from the following raw materials by weight percentage: 42~46wt% transparent polyether polyurethane, 32~36wt% epoxy modified acrylic resin, 5~7wt% purified water, 4~6wt% ethanol, 3~4wt% dimethylsiloxane, 2.5~3.5wt% polyethylene wax emulsion, 1wt% silicone defoamer, 2wt% silicone hand feel agent and 1.5wt% polyethylene oxide.

[0038] Figure 1 This application illustrates a method for preparing a tactile varnish according to an embodiment, including step S1.

[0039] S1: Mix transparent polyether polyurethane, epoxy-modified acrylic resin, water, ethanol, dimethylsiloxane, polyethylene wax emulsion, silicone defoamer, silicone hand feel agent and polyethylene oxide at room temperature until homogeneous.

[0040] Optionally, add it to a mixer, maintain the mixing temperature at about 25°C, and disperse it at a mixing speed of 800~1000r / min for 50~60min to obtain the final product.

[0041] The tactile light source provided in this application can be applied to packaging materials. A coating formed by tactile varnish can be printed onto paper or cardboard using a printing method. Before printing, the surface of the paper or cardboard needs to be covered with BOPP film, and the surface tension of the front side of the BOPP film needs to be greater than 35 (testing tool, 35# dyne pen).

[0042] This application uses transparent polyether polyurethane combined with epoxy-modified acrylic resin, and through the interaction of different component formulations, effectively solves the problems of poor abrasion and scratch resistance, easy color explosion at folds, and insufficient adhesion of tactile varnish applied to BOPP film. At the same time, its production process has the advantages of environmental protection, safety, and low volatility.

[0043] The tactile varnish provided in this application has a fast curing speed during application (printing process) and has excellent water resistance, hot water resistance, chemical resistance, anti-adhesion, toughness, strong tactile feel, good wear resistance, low volatility, energy saving and environmental protection, non-yellowing, low cost, and stable product quality, which is conducive to improving the decorative effect of packaging materials.

[0044] The present invention will now be described with reference to specific embodiments. The process conditions described in the following embodiments are exemplary, and their possible ranges are as shown in the foregoing description of the invention. For process parameters not specifically noted, conventional techniques can be used. Unless otherwise specified, the detection methods used in the following embodiments are conventional detection methods in the industry. Unless otherwise indicated, the reagents and instruments used in the technical solutions provided by the present invention can be purchased from conventional channels or the market.

[0045] Example 1

[0046] This embodiment prepares a printed product with a 230g printing white cardboard substrate covered with a BOPP film. The surface tension of the BOPP film is approximately 40 (measured using a 35# dyne pen). The specific preparation steps are as follows: Transparent polyether polyurethane, epoxy modified acrylic resin, water, ethanol, dimethylsiloxane, polyethylene wax emulsion, silicone defoamer, silicone hand feel agent and polyethylene oxide are added to the mixer according to the mass percentage in Table 1. The mixing temperature is kept at about 25°C and dispersed at a mixing speed of 900 r / min for 55 min to obtain the tactile varnish product. Then, a manual screen printing machine (150 mesh screen, 50 HA squeegee, 45° squeegee angle) is used to print the tactile varnish onto the substrate. During the production process, the varnish needs to be stirred every 10 minutes to ensure that the tactile varnish is evenly distributed. After screen printing, the product is first dried in an infrared oven, and then left to dry completely for 24 hours in a normal environment (28 ℃, 60% humidity) to obtain the printed product.

[0047] Table 1

[0048] Result evaluation: 1) Abrasion resistance test: a. Standard ASTM D5264; b. The size of the white book paper is 51x280mm, and the test sample is cut into 76*240mm pieces; c. Rub the 80g book paper and the printed matter together at a friction weight of 4 lbs, 100 rubs, and a friction speed of 85 rubs / minute; d. Observe that there are no obvious scratches on the sample and no obvious discoloration on the book paper.

[0049] 2) Anti-sticking test: a. Place the test sample under standard atmospheric conditions for 4 hours; b. Cut the test sample into 150*240mm pieces, fold them in half right side by side, then stack them into 75*240mm pieces and place them in the test chamber, pressing them with a 15KG iron block. c. Turn on the microcomputer constant temperature and humidity test chamber (60 ℃, 48 hours); d. After the test chamber stops running, take out the sample and observe for adhesion or stains after 2 hours.

[0050] 3) Anti-explosion color test: a. Place the test sample under standard atmospheric conditions for 4 hours; b. Cut the test sample into 200*300mm pieces; c. Use a die-cutting machine to perform crease processing; d. Fold the test sample 180 degrees from the crease 50 times and observe the color explosion.

[0051] 4) Tactile evaluation: a. Cut the test sample into 100*100mm pieces, 20 pieces in total; b. Mark all samples on the back and mix them together; c. Arrange 10 people to conduct blind touch tests and sort the tactile samples; d. Statistically analyze the tactile ranking results.

[0052] 5) Adhesion assessment: a. Cut the sample to be tested into 76*240mm pieces; b. Prepare 3M 600 standard test tape 19mm*33m; c. Paste the test tape onto the tactile coating surface (adhesion length 80mm), and press the adhesive surface firmly with the palm of your hand to smooth it; d. Quickly pull it up perpendicular to the adhesive surface and observe whether there is any coating peeling or bubbling or other abnormalities on the adhesive surface.

[0053] The test results are shown in Table 10.

[0054] Example 2

[0055] This embodiment prepares a printed product, which differs from Example 1 in the amount of raw materials used, as detailed in Table 2. The test results of the printed product are shown in Table 10.

[0056] Table 2

[0057] Example 3

[0058] This embodiment prepares a printed product, which differs from Example 1 in the amount of raw materials used, as detailed in Table 3. The test results of the printed product are shown in Table 10.

[0059] Table 3

[0060] Example 4

[0061] This embodiment prepares a printed product, which differs from Example 1 in the amount of raw materials used, as detailed in Table 4. The test results of the printed product are shown in Table 10.

[0062] Table 4

[0063] Example 5

[0064] This embodiment prepares a printed product, which differs from Example 1 in the amount of raw materials used, as detailed in Table 5. The test results of the printed product are shown in Table 10.

[0065] Table 5

[0066] Example 6

[0067] This embodiment prepares a printed product, which differs from Example 1 in the amount of raw materials used, as detailed in Table 6. The test results of the printed product are shown in Table 10.

[0068] Table 6

[0069] Comparative Example 1 This comparative example prepared a printed product, which differs from Example 1 in the raw materials, as detailed in Table 7. The test results of the printed product are shown in Table 10. The results of the abrasion resistance test, colorfastness test, and adhesion evaluation are attached. Figures 2-4 . Figures 2-4 The black, red, and yellow circles indicate scratches, color bleeding, and coating peeling on the adhesive surfaces.

[0070] Table 7

[0071] Comparative Example 2 This comparative example prepared a printed product, which differs from Example 1 in the raw materials, as detailed in Table 8. The test results of the printed product are shown in Table 10.

[0072] Table 8

[0073] Comparative Example 3 This comparative example prepared a printed product, which differs from Example 1 in the raw materials, as detailed in Table 9. The test results of the printed product are shown in Table 10.

[0074] Table 9

[0075] Table 10

[0076] This invention uses transparent polyether polyurethane as the coating material, which has a softer and fuller feel compared to ordinary polyester and polyurethane types, resulting in a more durable and shatter-resistant tactile varnish coating. It also overcomes the hot-stickiness and cold-brittleness drawbacks of acrylic resin, providing a soft and full feel. When transparent polyether polyurethane is blended with acrylic resin, it further enhances flexibility.

[0077] From Table 10 and Figures 2-4 It is evident that existing water-based polyurethane tactile oils exhibit poor adhesion, easy color fading, and unpleasant tactile feel at BOPP interfaces. This invention utilizes a combination of transparent polyether polyurethane and epoxy-modified acrylic resin, possessing polar macromolecular chain groups that react with polypropylene (C3H6). n The molecular chains cross-link under ultraviolet light, enhancing adhesion. Simultaneously, due to its high molecular weight, it improves the tactile feel. Furthermore, through the positive influence of other formulation components, it macroscopically exhibits the advantages of both acrylic and polyester resins, resulting in a significant improvement in tactile feel and abrasion resistance, and a qualitative improvement in adhesion to BOPP film.

[0078] Finally, it should be noted that the above descriptions are merely preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A tactile varnish, characterized in that, include: Transparent polyether polyurethane, epoxy-modified acrylic resin, ethanol, dimethylsiloxane, polyethylene wax emulsion, silicone defoamer, silicone feel agent and polyethylene oxide.

2. The tactile varnish according to claim 1, characterized in that, The raw materials include the following percentages by weight: 38-48 wt% transparent polyether polyurethane, 30-40 wt% epoxy modified acrylic resin, 3-9 wt% water, 3-8 wt% ethanol, 2-4.5 wt% dimethylsiloxane, 2-4.5 wt% polyethylene wax emulsion, 0.5-1.5 wt% silicone defoamer, 1.5-2.5 wt% silicone hand feel agent and 1-2 wt% polyethylene oxide.

3. The tactile varnish according to claim 2, characterized in that, Made from the following raw materials by weight percentage: 42~46wt% transparent polyether polyurethane, 32~36wt% epoxy modified acrylic resin, 5~7wt% purified water, 4~6wt% ethanol, 3~4wt% dimethylsiloxane, 2.5~3.5wt% polyethylene wax emulsion, 1wt% silicone defoamer, 2wt% silicone hand feel agent and 1.5wt% polyethylene oxide.

4. The tactile varnish according to claim 1, characterized in that, The molecular weight of the transparent polyether polyurethane is 2500~2800.

5. The tactile varnish according to claim 1, characterized in that, The epoxy-modified acrylic resin has a molecular weight of 75,000 to 78,000.

6. The tactile varnish according to claim 1, characterized in that, The concentration of the ethanol is greater than 90% wt.

7. The tactile varnish according to claim 1, characterized in that, The solid content of the polyethylene wax emulsion is 30~40wt%.

8. The use of the tactile varnish according to any one of claims 1 to 7 in packaging materials.

9. A printed product, characterized in that, It includes a coating formed by the tactile varnish as described in any one of claims 1 to 7.